2011
DOI: 10.1126/scitranslmed.3002621
|View full text |Cite
|
Sign up to set email alerts
|

A Peptidomimetic Targeting White Fat Causes Weight Loss and Improved Insulin Resistance in Obese Monkeys

Abstract: Obesity, defined as body mass index greater than 30, is a leading cause of morbidity and mortality and a financial burden worldwide. Despite significant efforts in the past decade, very few drugs have been successfully developed for the treatment of obese patients. Biological differences between rodents and primates are a major hurdle for translation of anti-obesity strategies either discovered or developed in rodents into effective human therapeutics. Here, we evaluate the ligand-directed peptidomimetic CKGGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 44 publications
3
89
0
1
Order By: Relevance
“…Thus, the manipulation of adipose tissues and vasculature may be a useful therapeutic strategy for treating metabolic diseases including obesity and diabetes. Previous studies in mouse and monkey models have shown that ligand-directed peptidomimetic compounds can induce apoptosis within the blood vasculature of white adipose tissue and result in rapid weight loss and improved insulin resistance (10,20). A few other studies demonstrated that methionine aminopeptidase inhibitors, fumagillin and beloranib, could induce sustained weight reduction by reducing the production of new fatty acids in the liver and reducing the pathological angiogenesis in adipose tissue (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the manipulation of adipose tissues and vasculature may be a useful therapeutic strategy for treating metabolic diseases including obesity and diabetes. Previous studies in mouse and monkey models have shown that ligand-directed peptidomimetic compounds can induce apoptosis within the blood vasculature of white adipose tissue and result in rapid weight loss and improved insulin resistance (10,20). A few other studies demonstrated that methionine aminopeptidase inhibitors, fumagillin and beloranib, could induce sustained weight reduction by reducing the production of new fatty acids in the liver and reducing the pathological angiogenesis in adipose tissue (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Few therapeutic agents are available for treating obesity in the clinic due to the complex interplay of genetic, environmental, and cultural factors (9). Previous studies have shown that modulations against vascular development in adipose tissues could alter tissue metabolism and inhibit the development of obesity in mice as well as monkeys (3,5,10). However, treating obesity with antiangiogenesis therapy has been hindered by the fact that energy expenditure in certain types of adipose tissue is critically dependent on angiogenesis (6), and an approach to differentially deliver an antiangiogenic agent to the adipose tissue has remained largely elusive.…”
mentioning
confidence: 99%
“…Adequate adipose tissue vascularization and blood flow are crucial to support adipocytes with nutrients and oxygen, and to maximize the efficiency of lipid uptake and/or release in response to variations in the nutritional state. Pharmacological inhibition of angiogenesis is associated with a significant reduction in adiposity in both mice and monkeys (Bråkenhielm et al, 2004;Cao, 2010;Barnhart et al, 2011;Sun et al, 2012). Interestingly, in pathological conditions such as obesity, adipose tissue grows independently of vascularization, leading to a poor oxygen and nutrient supply to adipocytes (Hosogai et al, 2007;Rausch et al, 2008;Yin et al, 2009;Kim et al, 2012).…”
Section: Development Of Vertebrate Adipose Tissuementioning
confidence: 99%
“…As the limitations of rodents, particularly mice, as models for use in studies of human cancer and obesity/diabetes become increasingly evident (109,110), the need for better animal models becomes increasingly urgent. Use of the White Leghorn laying hen as a model for ovarian cancer "By the year 2000 we will have developed an animal breeding system in which artificial insemination has been replaced by a system of artificial inembryonation.…”
Section: Assessment Of Future Developments In the Animal Industriesmentioning
confidence: 99%